2020
DOI: 10.1002/celc.202000176
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Cobalt Phosphite Nanorods Decorated with Carbon Nanotubes as Bifunctional Electrocatalysts in Alkaline Medium with a High Yield of Hydrogen Peroxide

Abstract: It is highly desirable to develop an energy generation system comprising a low-cost and earth-abundant non-noble metal catalyst for bifunctional electrocatalysis with good overall process performance, especially for applications in fuel cells or metal-air batteries. In this report, we show that nickel cobalt phosphite (NiCoÀ Phi) decorated with carbon nanotubes (CNTs) can perform as a bifunctional electrocatalyst for the oxygen evolution and oxygen reduction reactions (OER and ORR, respectively). The NiCoÀ Phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…This further supports effective OER for CP-1 than other compounds. The faradaic efficiency of CP-1 has been calculated as 91% using the RRDE 56 (Figure S18). To evaluate and compare the stability of CP-1, CP-2, and CP-3 electrocatalysts at the same current density, we have performed the i−t curve for CP-1 and CP-3 at an applied potential of 1.6 V versus RHE and CP-2 at 1.64 versus RHE.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This further supports effective OER for CP-1 than other compounds. The faradaic efficiency of CP-1 has been calculated as 91% using the RRDE 56 (Figure S18). To evaluate and compare the stability of CP-1, CP-2, and CP-3 electrocatalysts at the same current density, we have performed the i−t curve for CP-1 and CP-3 at an applied potential of 1.6 V versus RHE and CP-2 at 1.64 versus RHE.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the high-resolution Ni 2p spectrum (Fig. 2d) shows two primary peaks of Ni 2p 3/2 (855.6 eV) and Ni 2p 1/2 (873.1 eV) with two broad satellite peaks at 861.4 and 879.3 eV, confirming the existence of Ni 2+ [37,38]. Recent reports reported that Ni 2+ centers behave as the active sites for 2e − ORR, thus playing an important role in enhancing the ORR activity and tuning the selectivity [39].…”
Section: Resultsmentioning
confidence: 66%
“…Up to now, various nanostructured transition metal‐based materials such as CoS 2 , [113,114] Mn‐based oxides, [115,116] Fe 3 O 4 , [117] NiCo phosphite, [118] Co 3 O 4 , [119] and Zn‐based MOF [121] have been explored as efficient catalyst towards H 2 O 2 production through the ORR process. Moreover, transition metal compounds are often supported on conductive carbon nanomaterials to improve the conductivity and obtain uniformly dispersed transition metal compounds, thus improving the electrocatalytic performance.…”
Section: Two‐electron Orr Over Transition Metal‐based Materialsmentioning
confidence: 99%
“…The P−H group can promote interaction with H 2 O molecules, whereas the O−H group may endow stability in alkaline solution. Nickel cobalt phosphite nanorods/CNTs were synthesized hydrothermally, [118] and the ORR by the composites occurred mainly through the 2e − transfer process with an onset potential of 0.75 V and Tafel slope of 100 mV dec −1 in 0.1 M KOH with H 2 O 2 yield of 85 %. However, the mechanism of 2e − ORR process on doped‐transition metal phosphites is still unexplored.…”
Section: Two‐electron Orr Over Transition Metal‐based Materialsmentioning
confidence: 99%